'K is for Keeper': the roles and representations of the English gamekeeper, c. 1880–1914. Issue 1 (13th April 2022) - Ridgwell, Stephen
Abstract: The gamekeeper was an important but controversial presence in the late Victorian and Edwardian countryside. Admired by some for his skills in woodcraft and deep understanding of nature, for others the keeper was much less benign: a destroyer of wildlife; a barrier against wider public access to the land; and the upholder of fiercely contested laws. At a time when debates about the land and its present and future use formed a major part of contemporary political discourse, and when an urbanising society was investing ever more meaning in its idea of the rural, consideration of the keeper takes us beyond the study of field sports towards broader histories of the English countryside and its attendant ruralist culture. Situating the keeper in a dual setting of material production and recreational service provision, the following examines both what he did and was expected to do, and the ways in which this was represented. Not only were keepers active agents in their own representation, eager to project themselves as skilled professionals, they might also elicit support from unusual quarters. As will be seen, keeper representation was as varied as his many roles.